JURIDICAL ANALYSIS ON THE LEGAL CHOICE CLAUSE AND DISPUTE SETTLEMENT IN THE FRANCHISE AGREEMENT - Melianus T, Giovanni; Budiana, I Nyoman; Scolastika, Sheanny (Journal Equity of Law and Governance, 2021)
Collaboration in the trade sector both at the national and international levels in the form of a franchise looks simple, but behind it, there are various problems that require attention from both the public or parties as well as from the Indonesian government. This is because the franchise agreement conducted by the parties often involves foreign parties who have a different legal system from Indonesia. This situation has the potential to create a conflict of law. Therefore, this study aims to provide legal solutions to disputes that may occur between the franchisor and the franchisee so that neither parties is burdened because of the lack of laws covering it. Normative legal research is used to analysis the problem of this research. The data source of this research uses primary legal materials and secondary legal materials related to clauses in the franchise agreement. Likewise, for the settlement of disputes on an agreement that has not yet determined the choice of law, several theories in international civil law can be used, such as the lex loci contractus theory, the lex loci solutionis, the proper law of contract, and the theory of the most characteristic connection to find laws that should apply (lex cause) For the settlement of legal disputes (conflict of law), especially in franchise agreements, the settlement of disputes does not have to go through litigation or court but can be resolved through Alternative Dispute Resolution (ADR) including arbitration institutions, which have the advantage of solving them, namely efficiency ( cost and time).